Simultaneous determination of morazone and phenmetrazine in rat plasma and urine using an on-column injection technique with fused-silica capillary column gas chromatography - Lho, D.; Shin, H.; Park, J. (1990)
The simultaneous determination of morazone and its major metabolite, phenmetrazine, using an on-column injection technique with fused-silica capillary column gas chromatography is described. The on-column injection technique prevents the decomposition of morazone. The limit of quantitatlon in 0.1 mL of rat plasma for morazone and phenmetrazine is 5 ng/mL and that in 1.0 mL of rat urine is 1 ng/mL. The within run precislons (%CV) at the concentration of 0.5 μg/mL are 3.27% for morszone and 3.09% for phenmetrazine. ？ 1990 Oxford University Press.
Keywords: doping control; morazone; phenmetrazine; unclassified drug; animal experiment; article; blood; doping; drug determination; gas chromatography; methodology; nonhuman; priority journal; urine; Analgesics, Opioid; Animal; Antipyrine; Chromatography, Gas; Phenmetrazine; Rats; Reproducibility of Results; Animalia